Becoming an Innovative Islamic Education Teacher: Synergy of Teacherpreneurship and Community of Practice - Muhammad Nashihin (Global Journal of Islamic Education, 2026)
This study aims to analyze the synergy between the concepts of teacherpreneurship and Community of Practice (CoP) in improving the professionalism of Islamic Education (PAI) teachers at the elementary school and madrasah levels. The research method used is qualitative with a case study approach, involving observation, interviews, and documentation of the research subjects, which consist of PAI teachers, madrasah principals, education supervisors, and students. Data was collected through direct observation of teaching practices, in-depth interviews with key informants, and analysis of documentation related to learning activities and professional development. The results of the study indicate that the integration of teacherpreneurship and CoP has a positive impact on learning innovation and the improvement of PAI teachers' competencies. Teachers who develop entrepreneurial skills in the field of education are able to create creative teaching materials that are relevant to the needs of students. In addition, through active participation in CoP, teachers can share experiences, strategies, and solutions to challenges encountered in the learning process. The role of education supervisors as facilitators in forming and managing CoP has proven effective in strengthening collaboration and shared learning among teachers. The conclusion of this study is that the synergy between teacherpreneurship and CoP is an effective strategy in improving the professionalism of PAI teachers. Recommendations include the need for entrepreneurship training for teachers, strengthening the role of educational supervisors in forming CoPs, and support from madrasahs in providing facilities and time for collaborative activities. Thus, it is hoped that PAI teachers can be more adaptive and innovative in facing the dynamics of education in the digital era.